Comparative Analysis of Bioacoustic and Point Count Methods for Calculating Bird Species Richness in Bukit Watu Ondo, Mount Ungaran, Central Java - Divanda Lathiifanindya; Vika Widyaningrum; Yudistira Nurpratama; Maesa Faradina; Ni’mah Alawiyah Safitri; Margareta Rahayuningsih (Journal of Biodiversity and Biotechnology, 2025)
The study aims to compare the effectiveness of bioacoustic and point count methods in assessing bird species richness in Bukit Watu Ondo, Mount Ungaran, Central Java. A quantitative approach was employed through simultaneous data collection using both methods at six observation points. Bird observations were conducted visually and acoustically for 15-minute sessions at each point, repeated three times. The data were analyzed using a paired t-test to determine statistical differences between the two methods. Results showed that the point count method identified 29 species from 22 families, while the bioacoustic method recorded 25 species from 17 families. Statistical analysis revealed no significant difference (p = 0.927) between the two methods in the number of detected species, indicating comparable effectiveness. However, bioacoustics proved more efficient in detecting vocally active or cryptic species that were difficult to observe visually, whereas point count performed better for visually conspicuous species. The combination of both methods provided a more comprehensive representation of avifaunal diversity. These findings demonstrate that bioacoustic techniques are a viable and complementary alternative to traditional visual methods in biodiversity monitoring and conservation management.